2020
DOI: 10.3390/app10113747
|View full text |Cite
|
Sign up to set email alerts
|

Auralization of High-Order Directional Sources from First-Order RIR Measurements

Abstract: Can auralization of a highly directional source in a room succeed if it employs a room impulse response (RIR) measurement or simulation relying on a first-order directional source, only? This contribution presents model and evaluation of a source-and-receiver-directional Ambisonics RIR capture and processing approach (SRD ARIR) based on a small set of responses from a first-order source to a first-order receiver. To enhance the directional resolution, we extend the Ambisonic spatial decomposition method (ASDM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Applying the PIV is especially straightforward if first-order Ambisonics room impulse responses (ARIR) are available. In broadband methods employing PIV estimation [4], [16], [17], the omnidirectional pressure is simply multiplied with the three first-order directional components sample-by-sample. The resulting vector's length can be interpreted as an estimate of diffuseness, which in turn is used in narrowband processing of SRIR [1] and in the parametric time-frequency spatial audio method DirAC [18], which operates on running signals.…”
Section: B Tdoa and Piv Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the PIV is especially straightforward if first-order Ambisonics room impulse responses (ARIR) are available. In broadband methods employing PIV estimation [4], [16], [17], the omnidirectional pressure is simply multiplied with the three first-order directional components sample-by-sample. The resulting vector's length can be interpreted as an estimate of diffuseness, which in turn is used in narrowband processing of SRIR [1] and in the parametric time-frequency spatial audio method DirAC [18], which operates on running signals.…”
Section: B Tdoa and Piv Estimationmentioning
confidence: 99%
“…Firstly, it has been observed that the rendered response may contain more high frequencies than the omnidirectional response, which can be referred to as whitening. The effect has first been reported in [29] and the typical solution is to apply spectrogram or filterbank-based time-varying equalization to the response [17], [29]. If such equalization is not done carefully, it can lead to audible artefacts of its own.…”
Section: Analysis Of a Real Spacementioning
confidence: 99%
“…For directional sound sources and receivers, it is also important to consider the propagation path's direction of departure (DOD) from the source and direction of arrival (DOA) at the receiver [35]. They are denoted by Ω s = (ϕ s , θ s ) and Ω r = (ϕ r , θ r ), respectively, where ϕ is the azimuth angle and θ is the elevation angle.…”
Section: Introductionmentioning
confidence: 99%
“…A room impulse response (RIR) describes the combined effects on sound waves traveling from a sound source at position x s = (x s , y s , z s ) to a receiver at position x r = (x r , y r , z r ). For directional sound sources and receivers, it is also important to consider the propagation path's direction of departure (DOD) from the source and direction of arrival (DOA) at the receiver [43]. They are denoted by Ω s = (ϕ s , θ s ) and Ω r = (ϕ r , θ r ), respectively, where ϕ is the azimuth angle and θ is the elevation angle.…”
Section: Introductionmentioning
confidence: 99%